2020
DOI: 10.1371/journal.pone.0230513
|View full text |Cite
|
Sign up to set email alerts
|

Variability in tactical behavior of futsal teams from different categories

Abstract: The aim of the present study was to analyze the time series of team spread during futsal official matches in the frequency domain for different categories. Using an automatic tracking method, trajectories of 258 players (excluding goalkeepers) were obtained, composed of 79 players from the under-15 (U15) category, 86 from the under-18 (U18), and 93 from the professional. We calculated the team spread defined as the Euclidean norm of the distancebetween-player vector as a function of time. We applied the Fast F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The effort required for each player depends on several factors such as playing position, tactical functions, technical abilities, team strategies, and competitive levels (De Bueno et al, 2020;Caetano et al, 2015;Makaje et al, 2012;Méndez et al, 2019). Therefore, continuous and individual assessment of physical performance, as well as the heart rate (HR) variation during the game, is useful for the clear characterization of individual adaptations to training or even to monitor maladaptation during the process (Boullosa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The effort required for each player depends on several factors such as playing position, tactical functions, technical abilities, team strategies, and competitive levels (De Bueno et al, 2020;Caetano et al, 2015;Makaje et al, 2012;Méndez et al, 2019). Therefore, continuous and individual assessment of physical performance, as well as the heart rate (HR) variation during the game, is useful for the clear characterization of individual adaptations to training or even to monitor maladaptation during the process (Boullosa et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the assessment of players' organization on the court and the variability of their movements during the game have been found to be essential to understand the team collective behaviors in this sport (29). The knowledge of tactical competition demands can be used to design training strategies to replicate tactical responses in competition and optimizing the players' physical performance (9,27,35,38). However, few studies have analyzed the collective tactical behaviors and their relationship with physical demands during official futsal competition conditions and the more frequent situations during the game such as 2 teams of 4 players and 1 goalkeeper (29).…”
Section: Introductionmentioning
confidence: 99%
“…Futsal is a team invasion sport that has specific physical requirements with complex tactical behaviors (9,37), which are determined by different constraints such us the number of players (10) or the dimensions of the playing court (40 3 20 m) and different contextual variables of the game (29,31). For physical demands, previous studies have revealed a profile with intermittent high-intensity activities and a great number of acceleration (Acc) and deceleration (Dec), with short recovery times between them during the game (27,35,37).…”
Section: Introductionmentioning
confidence: 99%